Introduction to Dynamics - Pfeiffer, Friedrich (Springer, 2016)
This concise textbook for students preferably of a postgraduate level, but also for engineers in practice, contains the basic kinematical and kinetic structures of dynamics together with carefully selected applications. The book is a condensed introduction to the fundamental laws of kinematics and kinetics, on the most important principles of mechanics and presents the equations of motion in the form of Lagrange and Newton-Euler. Selected problems of linear and nonlinear dynamics are treated, as well as problems of vibration formation. The presented selection of topics gives a useful basis for stepping into more advanced problems of dynamics. The contents of this book represent the result of a regularly revised course, which has been and still is given for masters students at the Technische Universität München.